2008
DOI: 10.2202/2161-2412.1033
|View full text |Cite
|
Sign up to set email alerts
|

African American Students and No Child Left Behind Legislation: Progression or Digression in Educational Attainment

Abstract: The No Child Left Behind (NCLB) federal legislation has dramatically changed the way schools and school districts measure educational attainment for all students. In this article, the researchers examine whether African Americans have progressed or digressed in their educational attainment five years after the implementation of NCLB. To provide a clear picture on the status of educational attainment for African American K?12 public school students across the United States, an analysis of data from the National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Accordingly, race/ethnicity and gender are important factors that relate to student learning in mathematics. Although current research has documented a slight narrowing in overall race/ethnicity and gender gaps in mathematics (Lewis, Hancock, James, & Larke, 2008;National Indian Education Study 2007;Tomsho, 2009;U.S. Department of Education, 2008) inequalities still exists today (Lewis et al, 2008;Thernstrom & Thernstrom, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, race/ethnicity and gender are important factors that relate to student learning in mathematics. Although current research has documented a slight narrowing in overall race/ethnicity and gender gaps in mathematics (Lewis, Hancock, James, & Larke, 2008;National Indian Education Study 2007;Tomsho, 2009;U.S. Department of Education, 2008) inequalities still exists today (Lewis et al, 2008;Thernstrom & Thernstrom, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Since the implementation of No Child Left Behind (NCLB), students of color have been identified as low achieving when compared to their white counterparts (Howard, 2006;Howard, 2010;Lewis, Hancock, James, Larke, 2008;Nieto, 2004). Research on CRRI has shown increased achievement with diverse student populations (Howard, 2008).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…The current status of African American students in the American public school educational system has been and continues to be a priority in educational research (Lewis, Hancock, James, and Larke, 2008;Darling-Hammond, 2005;Noguera, 2008;Ladson-Billings, 1995). From the perspectives of , African American students have been -shortchanged by elementary and secondary schools in the United States‖ (p. 10).…”
Section: Introductionmentioning
confidence: 99%